INFLUENZA SURVEILLANCE IN MALAYSIA: 1997 -2001 - Nor Shahidah; Ismail Merican; Raman lsmail (Malaysian Journal of Public Health Medicine, 2003)
Influenza has always been wrongly perceived as a minor disease which is no different than common cold. Influenza affecting all age groups cause a considerable morbidity and mortality although the data are not well established in the Asia Pacific. In the United States, it claims similar order of mortality as that due to car accidents. Influenza A and B can cause epidemic human disease. New Influenza virus variants develop frequently due to antigenic drift. The rapid evolution of both influenza A and B virus is responsible for annual influenza epidemics in humans. Although in Malaysia, Influenza Surveillance began in 1954, the disease awareness is still low. It is prudent to continue the surveillance throughout in order to monitor the seasonal trend, circulating strain as well to prepare us from an epideniic or pandemic. Institute for Medical Research, being the sole WHO National Reference lab in this country committed in improving the Influenza Surveillance which will involve. all the states in Malaysia in the near future.